Transkranielle Sonografie der Insula: Digitalisierte Bildanalyse der Fusionsbilder mit Magnetresonanztomografie - Školoudík, D; Bártová, P; Mašková, J; Dušek, P; Blahuta, J; Langová, K; Walter, U; Herzig, R (Ultraschall in der Medizin, 2016)
Purpose: Transcranial B-mode sonography (TCS) of brain parenchyma is increasingly used as a diagnostic tool for movement disorders. Accordingly, experimental B-Mode Assist software was developed to enable digitized analysis of the echogenicity of predefined brain regions. The aim of the study was to assess the reproducibility of digitized TCS image analysis of the insula. Materials and Methods: A total of 130 patients with an indication for neurosonological examination were screened for participation in the study. The insula was imaged from the right temporal bone window using Virtual Navigator and TCS-MRI (magnetic resonance imaging) fusion imaging. All subjects were examined three times by two experienced sonographers. Corresponding images of the insula in the axial thalamic plane were encoded and digitally analyzed. Interclass correlation coefficient (ICC) and Spearman's rank correlation coefficient were used for the assessment of intra- and inter-reader as well as intra- and inter-investigator reliabilities. Results: TCS images of 114 patients were evaluated (21 patients with TIA, 53 patients with headache, 18 patients with essential tremor, 22 patients with neurodegerative disease). 16 patients were excluded from analysis due to insufficient bone window. The intra-reader, inter-reader, intra-investigator and inter-investigator ICCs/Spearman's rank correlation coefficients were 0.995/0.993, 0.937/0.921, 0.969/0.961 and 0.875/0.858, resp. Conclusion: The present study demonstrates a high reliability to reproduce echogenicity values of the insula using digitized image analysis and TCS-MRI fusion images with almost perfect intra-reader, inter-reader, intra-investigator and inter-investigator agreement.
Keywords: bolesti hlavy; tranzitorní ischemická ataka; uživatelské rozhraní počítače; User-Computer Interface; magnetická rezonanční tomografie; kontrastní látky; ultrasonografie dopplerovská transkraniální; Image Interpretation, Computer-Assisted; Neurodegenerative Diseases; Pregnancy; těhotenství; statistika jako téma; mozková kůra; thalamus; Observer Variation; reprodukovatelnost výsledků; Multimodal Imaging; Ultrasonography, Doppler, Transcranial; Reproducibility of Results; novorozenec; neurodegenerativní nemoci; Ischemic Attack, Transient; odchylka pozorovatele; Image Enhancement; lidé; ženské pohlaví; multimodální zobrazování; Contrast Media; Humans; Infant, Newborn; Headache; interpretace obrazu počítačem; Essential Tremor; Thalamus; Magnetic Resonance Imaging; vylepšení obrazu; Female; Statistics as Topic; esenciální tremor; Cerebral Cortex